1986
DOI: 10.1152/ajpheart.1986.251.5.h1076
|View full text |Cite
|
Sign up to set email alerts
|

Alpha 1-adrenergic stimulation of rat myocardial cells increases protein synthesis

Abstract: The effects of adrenergic stimulation on the rates of protein synthesis, degradation, and accumulation were examined in primary cultures of neonatal rat heart cells. Treatment of myocardial cells with norepinephrine increased total cellular protein content and the rate of incorporation of radiolabeled tyrosine into trichloroacetic acid insoluble protein. alpha 1-Adrenergic, but not alpha 2- or beta-adrenergic blockade, inhibited these norepinephrine induced increases. The rate of protein synthesis estimated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

1988
1988
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 0 publications
0
41
0
2
Order By: Relevance
“…MLC-2 is one of the contractile proteins of the cardiac myosin and has been reported to be a useful marker for cardiac hypertrophy (Meidell et al, 1986;Lee et al, 1988;Sen et al, 1988;Henderson et al, 1989;Doud et al, 1995). For example, spontaneous cardiac hypertrophy in rats is accompanied by increases in the amount of MLC-2 mRNA (Lee et al, 1988), and -adrenergic stimulation of neonatal rat myocardial cells produces several features of myocardial hypertrophy, including a several-fold increase in the volume of the MLC-2 gene (Kummar et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MLC-2 is one of the contractile proteins of the cardiac myosin and has been reported to be a useful marker for cardiac hypertrophy (Meidell et al, 1986;Lee et al, 1988;Sen et al, 1988;Henderson et al, 1989;Doud et al, 1995). For example, spontaneous cardiac hypertrophy in rats is accompanied by increases in the amount of MLC-2 mRNA (Lee et al, 1988), and -adrenergic stimulation of neonatal rat myocardial cells produces several features of myocardial hypertrophy, including a several-fold increase in the volume of the MLC-2 gene (Kummar et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The amounts ofmyosin heavy chain (Waspe et al,1990), -actin (Bishopric et al, 1987), and myosin light chain-2 (MLC-2; Kummar et al, 1986) increase 3, 4, and 4 times, respectively. Among these contractile proteins, MLC-2, one of the cardiac myosin molecules (Emerson and Bernstein, 1987), has been used extensively as a marker protein for myocardial hypertrophy (Meidell et al, 1986;Lee et al, 1988;Sen et al, 1988;Henderson et al, 1989;Doud et al, 1995). Phosphorylation of MLC-2 modulates the contractile activity of cardiac cells (Silver et al, 1986;Stull et al, 1985;Morano, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Cell Culture-Rat neonatal cardiac myocytes were prepared as described previously (17). Briefly, the hearts were isolated from 1-day-old HLA-Wistar rats.…”
Section: Construction Of Epitope-taggedmentioning
confidence: 99%
“…It has been suggested that the a,-adrenoceptor-mediated response may become important under certain pathological conditions including ischaemia (Penny et al, 1985), abnormal thyroid function (Williams et al, 1977), dysrhythmogenesis (Sheridan et al, 1980) and hypertension (Yamada et al, 1984). ajAdrenoceptors may also be involved in other processes such as protein synthesis (Meidell et al, 1986) and cardiac hypertrophy (Simpson, 1990). Radioligand binding studies have been performed on several myocardial preparations (Williams & Lefkowitz, 1978;Rugevics & Schumann, 1987;Bevilacqua et al, 1987;Steinkraus et al, 1989;Shen et al, 1989) revealing intra-and interspecies differences in the density of cladrenoceptors which might partially be due to different experimental conditions.…”
Section: Introductionmentioning
confidence: 99%